Mortgage Krizi Öncesi ve Sonrasında Enflasyon - Faiz Etkileşimi: Türkiye Örneği - Akcan, Ahmet Tayfur (Muş Alparslan Üniversitesi, 2019)
The relationship between inflation and interest rates is thesubject of many studies. These studies are mostly about the Fisher Hypothesis.The Fisher hypothesis suggests that the nominal interest rate and the inflationrate will be in a long-run relationship under the assumption that real interestrates will not change. In this study, the causality relationship betweeninflation and unemployment and the validity of the Fisher Hypothesis wereinvestigated before and after the mortgage crisis. June 2000 - September 2007and October 2007 - October 2018 Monthly data were analyzed by Augmented DickeyFuller Root Test, Johansen Cointegration Test and Granger Causality Test.According to the results of the study; The Fisher Hypothesis is valid before, after the crisis and during June 2000 – October 2018. However, the two-waycausality relationship between the variables before the mortgage crisis waslost after the crisis. The causality relationship from interest rates toinflation was determined between June 2000 – October 2018.

Enflasyon ve faiz oranları arasındaki ilişki birçokçalışmanın konusunu oluşturmaktadır. Bu çalışmalarda çoğunlukla Fisher Hipoteziüzerinedir. Fisher Hipotezi, reel faiz oranlarının uzun dönemde değişmeyeceğivarsayımında, nominal faiz ile beklenen enflasyon oranının uzun dönemli ilişkiliolacağını ileri sürmektedir. Çalışmada, Mortgage krizi öncesi ve sonrasındaenflasyon ve işsizlik arasındaki nedensellik ilişkisi ve Fisher Hipoteziningeçerliliği araştırılmıştır. Haziran 2000 – Eylül 2007 ve Ekim 2007 – Ekim 2018arası aylık veriler Augmented Dickey Fuller Birim Kök, Johansen Eşbütünleşme, veGranger Nedensellik Testi ile analiz edilmiştir. Çalışmanın sonuçlarına göre;Mortgage Krizi öncesi, sonrası ve 2000-2018 arasında Fisher Hipotezigeçerlidir. Ancak Mortgage krizi öncesi değişkenler arasında var olan çiftyönlü nedensellik ilişkisi kriz sonrasında kaybolmuştur. 2000-2018 dönemiarasında ise faiz oranlarından enflasyona doğru nedensellik ilişkisi tespitedilmiştir.
Inflation – Interest Interaction Before and After the Mortgage Crisis: the Case of Turkey
anemon
Keywords: Fisher Hypothesis; Inflation; Interest; Causality; Fisher Hipotezi; Enflasyon; Faiz; Nedensellik